KOMUNIKASI TOKOH MASYARAKAT RURAL DALAM MEMBANGUN DAERAHNYA PENGKAJIAN DI KECAMATAN GANTIWARNO, PRAMBANGAN, BAYAT, CAWAS, KABUPATEN KLATEN, JAWA TENGAH, 2007 - Gunadi, YS (Universitas Prof. Dr. Moestopo (Beragama), 2008)
The vallage is the represent home stay somewhere permanently of the big society as rural districts. They are do on the tradisional landscape to plantation rises or plantation another plan agricultures. There are manies material to be served for economic people market enough in their lives. But, untl now prosperity group of the farmes still upset indisonder guided information leader. Official Information Leaders of Agricultural of Subdistricts (PPL) not yet rolling information to the famers. Reason its, because their himself lessknowledge and lesssciencies about agricultural system like the coment anather farmers. Its cosequences, group of the farmers not can run away to the modernization technology agriculture. From it, the farmers still poor misernstion in their life..